Il teatro è un’arte visiva? (Itinera, 2013)
Is theatre a visual art? We can consider such a question from a double point of view. From a practical perspective the answer seems to be posi-tive, however in theoretical terms the question is more complicated. The western idea of theatre is focused on the primacy of literary and it is only during the XX Century that the aesthetic consideration of theatre chang-es radically. Theater reduces or denies the narrative destination of its communication and emphasizes the production of an iconic meaning. Therefore we can speak of two different kinds of scenic dramaturgy: the “dramaturgy of difference” when we have a free interpretation of a preex-istent literary text (as for Jerzy Grotowski or Carmelo Bene) and an “iconic dramaturgy” (as for Romeo Castellucci or Jan Fabre) when we have the autonomous construction of a visual dramaturgy.